2010 IEEE Computer Society Conference on Computer Vision and Pattern Recognition - Workshops 2010
DOI: 10.1109/cvprw.2010.5544605
|View full text |Cite
|
Sign up to set email alerts
|

Complex spectral minutiae representation for fingerprint recognition

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…The orientation θ of a minutia can be incorporated by using the spatial derivative of m(x, y) in the direction of the minutia orientation. Thus, to every minutia in a fingerprint, a function m i (x, y, θ) is assigned being the derivative of m i (x, y) in the direction θ i , such that (4) As with the SML algorithm, using a Gaussian filter and taking the magnitude of the spectrum yields (5) Recently, (Xu & Veldhuis, 2010) have further discussed the objective of the spectral minutiae representation in representing a minutiae set as a fixed-length feature vector that is invariant to translation, rotation and scaling. Fig.…”
Section: Ridge Orientation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation θ of a minutia can be incorporated by using the spatial derivative of m(x, y) in the direction of the minutia orientation. Thus, to every minutia in a fingerprint, a function m i (x, y, θ) is assigned being the derivative of m i (x, y) in the direction θ i , such that (4) As with the SML algorithm, using a Gaussian filter and taking the magnitude of the spectrum yields (5) Recently, (Xu & Veldhuis, 2010) have further discussed the objective of the spectral minutiae representation in representing a minutiae set as a fixed-length feature vector that is invariant to translation, rotation and scaling. Fig.…”
Section: Ridge Orientation Approachmentioning
confidence: 99%
“…14 illustrates a general procedure of the spectral minutiae representation discussed by (Xu & Veldhuis, 2010). (Xu & Veldhuis, 2010) Moreover, based on the spectral minutiae feature, (Xu et al, 2009a(Xu et al, , 2009b introduced two feature reduction methods: the Column-Principal Component Analysis (PCA) and the LineDiscrete Fourier Transform feature reduction algorithms. The experiments demonstrated that these methods decrease the minutiae feature dimensionality with a reduction rate of 94%, while at the same time, the recognition performance of the fingerprint system is not degraded.…”
Section: Ridge Orientation Approachmentioning
confidence: 99%
“…Recently, the spectral minutiae representation [1][2] has shown its power in minutiae-based fingerprint recognition, which can handle minutiae translation and rotation and improve matching speed, satisfying properties required by high-resolution palmprint recognition as well. As defined in [1], the method uses the minutiae locations in spatial domain and takes Fourier transform of the coded locations and obtains the magnitude of its Fourier spectrum in frequency domain.…”
Section: Introductionmentioning
confidence: 99%
“…As defined in [1], the method uses the minutiae locations in spatial domain and takes Fourier transform of the coded locations and obtains the magnitude of its Fourier spectrum in frequency domain. The three types of spectral minutiae representations are the location-based spectral minutiae representation (SML), the orientation-based spectral minutiae representation (SMO) and the complex spectral minutiae representation (SMC), among which the enhanced SMC method [2] performs best for fingerprints with the EER of 3.05% on FVC2002 DB2A 1 database and a matching speed of 8000 comparisons per second.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation